Electronic band structure of Mg-IV- N2 compounds in the quasiparticle-self-consistent GW approximation - Jaroenjittichai A. (2017)
© 2016 American Physical Society. We present calculations of the lattice constants, structural parameters, bulk moduli, energies of formation, and band structures of Mg-IV-N2 compounds with IV=Si, Ge, Sn by using the full-potential linearized muffin-tin orbital method and the quasiparticle-self-consistent GW approach for the wurtzite-based Pna21 crystal structure. The lattice parameters calculated with the generalized gradient approximation (GGA) are found to be in good agreement (within 1%) with experiment for the cases of MgSiN2 and MgGeN2, where data are available. Similar to the Zn-IV-N2 compounds, MgSiN2 is found to have an indirect gap slightly lower than the lowest direct gap, while the other materials have direct gaps. The direct gaps, calculated at the GGA lattice constant, range from 3.43 eV for MgSnN2 to 5.14 eV for MgGeN2 and 6.28 eV for MgSiN2 in the 0.8Σ approximation, i.e., reducing the QSGWΣ by a factor 0.8 and including an estimated zero-point-motion correction. The symmetry character of the valence-band maximum states and their splittings and effective masses are determined. The conduction-band minima are found to have slightly higher Mg s- than Si s-like character in MgSiN2 but in MgGeN2 and MgSnN2, the group-IV-s character becomes increasingly dominant.